Successful Pregnancy and Delivery in a Patient with Chronic Myeloid Leukemia while on Dasatinib Therapy. (22nd February 2010) - Conchon, Monika; Sanabani, Sabri S.; Serpa, Mariana; Novaes, Mafalda M. Y.; Nardinelli, Luciana; Ferreira, Patrícia B.; Dorliac-Llacer, Pedro Enrique; Bendit, Israel
Abstract : Here we report the case of an 18-year-old woman with chronic myeloid leukemia (CML) who became pregnant while undergoing treatment with dasatinib. Before pregnancy, she received imatinib mesylate therapy but could not tolerate the treatment. The regimen was then changed to dasatinib at a dose of 70 mg b.i.d. While she was in hematological remission and on dasatinib therapy, she became pregnant. The unplanned pregnancy was identified after the patient had experienced four weeks of amenorrhea. Because the patient elected to continue the pregnancy to term, dasatinib was stopped immediately. Meanwhile, CML hematological relapse occurred and then she was treated with interferon-α (IFN-α ) (9 million IU/day) throughout the pregnancy without a complete hematological response. She successfully gave birth to a male baby at 33 weeks by cesarean section delivery with no sequelae or malformations. Although this experience is limited to a single patient, it provides a useful contribution for counselling patients inadvertently exposed to dasatinib during pregnancy.